TEACHING STUDENTS TO INDEPENDENT THINKING AND CREATIVITY THROUGH INTERACTIVE METHODS IN PRIMARY CLASS MOTHER LANGUAGE LESSONS (Web of Teachers: Inderscience Research, 2024)
The article discusses resourcefulness in learning adjective vocabulary in native language classes, ways to teach students independent thinking and creativity through various interactive games.